2019
DOI: 10.1088/1361-648x/ab161e
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and transport properties of Zr1−x Nb x Co2Sn

Abstract: ZrCo2Sn is a potential candidate as a Weyl semimetal with a ferromagnetic ground state, and Nb-doping is expected to shift the Weyl points to the vicinity of Fermi level. We successfully synthesized a series of Zr1−xNbxCo2Sn single crystals with various concentrations of Nb (x  =  0, 0.1, 0.2, 0.275, 0.4, 0.5). All samples have a spinel structure and the lattice constant decrease as the Nb doping level increases. The magnetization and transport measurements suggest that the ferromagnetic ordering temperature c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In contrast, we observed that the T C and µ sat slightly increase until x = 0.35 in Zr 1−x V x Co 1.6 Sn, which conforms to the well-know Slater-Pauling rule [36] but contradicts the expectation. Please note this T C change is also distinguished from the case of Zr 1−x Nb x Co 2 Sn [25] in which the Nb substitution leads to the weakening of ferromagnetism. This unexpected change of magnetization in our case is consistent with the previous studies on Co 2 Ti 1−x V x Sn [37,38] in which the saturation magnetization initially increases with x until x = 0.4 and then drops.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In contrast, we observed that the T C and µ sat slightly increase until x = 0.35 in Zr 1−x V x Co 1.6 Sn, which conforms to the well-know Slater-Pauling rule [36] but contradicts the expectation. Please note this T C change is also distinguished from the case of Zr 1−x Nb x Co 2 Sn [25] in which the Nb substitution leads to the weakening of ferromagnetism. This unexpected change of magnetization in our case is consistent with the previous studies on Co 2 Ti 1−x V x Sn [37,38] in which the saturation magnetization initially increases with x until x = 0.4 and then drops.…”
Section: Discussionmentioning
confidence: 91%
“…[16] However the AHE of the pristine and Nb-substituted ZrCo 2 Sn has not been analyzed thoroughly, although the single crystal growth, magnetic and electric transport properties have been reported. [23][24][25] Realizing the difficulty for growing single-crystalline TiCo 2 Sn, [26,27] we successfully grew single crystals of Zr 1−x V x Co 1.6 Sn with the L2 1 Heusler phase structure from molten tin flux. We found that their Curie temperature and magnetic moment are enhanced by V-substitution while the resistivity changes from bad-metal-like to semiconductor-like at x = 0.35.…”
Section: Introductionmentioning
confidence: 99%
“…The relaxed lattice parameter a is equal to 2.79 Å and lattice parameter b is 3.92 Å, which are strongly consistent with the values in previous work. [ 39 ] The unit cell of the puckered structure contains two C and two S atoms, and every C(S) atom is combined with the other S (C) three neighboring atoms by covalent bonds. Different from the atom arrangement distributed on two parallel planes in BP as shown in Figure S1, Supporting Information, the C and S atoms in monolayer α‐CS tend to slightly move beyond the two planes (forming four parallel planes) due to the difference of the atomic radii and electronegativity between C and S elements.…”
Section: Resultsmentioning
confidence: 99%
“…[ 38 ] An isoelectronic material α‐CS has been theoretically explored by density functional theory (DFT). [ 39,40 ] Previous works reported monolayer α‐CS has a moderate band gap of 1.11 eV and high mobilities (8500 cm 2 V −1 s −1 ). Moreover, monolayer α‐CS is predicted to be highly stable under 1000 K and can maintain the structural stability in water at 300 K. [ 39 ] However, the previous researches of 2D α‐CS just focused on the fundamental atomic structure, mechanical properties, and electronic properties, and the simulations of its device performance are still blank.…”
Section: Introductionmentioning
confidence: 99%
“…Although, for most of the proposed Heusler WSMs, the Weyl nodes lie away from the Fermi energy, which reduces the topological properties of these materials [27,28,[39][40][41][42]. By tuning the Fermi energy, it can coincide with the energy of the nodes, which can significantly improve the properties [41,43,44].…”
Section: Introductionmentioning
confidence: 99%